Synthesizing a novel genetic sequential logic circuit: a push‐on push‐off switch - Chunbo Lou; Xili Liu; Ming Ni; Yiqi Huang; Qiushi Huang; Longwen Huang; Lingli Jiang; Dan Lu; Mingcong Wang; Chang Liu; Daizhuo Chen; Chongyi Chen; et al. (Molecular Systems Biology, 2010)
Abstract Design and synthesis of basic functional circuits are the fundamental tasks of synthetic biologists. Before it is possible to engineer higher‐order genetic networks that can perform complex functions, a toolkit of basic devices must be developed. Among those devices, sequential logic circuits are expected to be the foundation of the genetic information‐processing systems. In this study, we report the design and construction of a genetic sequential logic circuit in Escherichia coli. It can generate different outputs in response to the same input signal on the basis of its internal state, and ‘memorize’ the output. The circuit is composed of two parts: (1) a bistable switch memory module and (2) a double‐repressed promoter NOR gate module. The two modules were individually rationally designed, and they were coupled together by fine‐tuning the interconnecting parts through directed evolution. After fine‐tuning, the circuit could be repeatedly, alternatively triggered by the same input signal; it functions as a push‐on push‐off switch.